Atomic photoionization experiment by harmonic-generation spectroscopy - Frolov, M. V.; Sarantseva, T. S.; Manakov, N. L.; Fulfer, K. D.; Wilson, B. P.; Troß, J.; Ren, X.; Poliakoff, E. D.; Silaev, A. A.; Vvedenskii, N. V.; Starace, Anthony F.; Trallero-Herrero, C. A. (My University, 2016)
Measurements of the high-order-harmonic generation yield of the argon (Ar) atom driven by a strong elliptically polarized laser field are shown to completely determine the field-free differential photoionization cross section of Ar, i.e., the energy dependence of both the angle-integrated photoionization cross section and the angular distribution asymmetry parameter.